2016
DOI: 10.1590/2359-3997000000068
|View full text |Cite
|
Sign up to set email alerts
|

PEG-asparaginase induced severe hypertriglyceridemia

Abstract: SUMMARYAsparaginase (ASP) is an effective chemotherapy agent extensively used in children with acute lymphocytic leukemia (ALL). There has been a recent interest in using ASP in adults with ALL, particularly the less toxic pegylated (PEG) formulation. Hypertriglyceridemia (HTG) is a rare complication of PEG-ASP therapy. We report two cases of obese patients who developed severe HTG after receiving PEG for ALL. Both patients were incidentally found to have severe HTG (TG of 4,330 and 4,420 mg/dL). In both patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
(35 reference statements)
1
13
0
2
Order By: Relevance
“…Pharmacological treatment of HTG. 12,35,36 and obese patients were more likely to develop severe HTG, however, the difference was not statistically significant. 4…”
Section: Peg/l-asp Re-challengementioning
confidence: 74%
See 2 more Smart Citations
“…Pharmacological treatment of HTG. 12,35,36 and obese patients were more likely to develop severe HTG, however, the difference was not statistically significant. 4…”
Section: Peg/l-asp Re-challengementioning
confidence: 74%
“…Reducing dietary fat and simple carbohydrates are a first line recommendation for HTG. 12,35 Other therapeutic strategies include an insulin infusion, heparin infusion, or plasmapheresis. 12 Three pharmacological classes are available for HTG treatment: fibrates, niacin, and omega-3 fatty acids ( Table 3).…”
Section: Pharmacologic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…As BMI was not different between patients and controls, we argue that this finding is likely related to changes in lifestyle, with reduced physical activity (3, 4), but we cannot exclude that the treatment with antineoplastic agents partially account for the fat accumulation. In fact treatment of ALL, beyond its acknowledged effect on IR, has been reported to cause derangement of lipid profile, in particular during steroids and asparaginase administration (59,60,61), and even though this toxic effect seems to be transient, long-term follow-up of patients with history of severe hypertriglyceridemia is recommended to better understand additional therapy-related risk factors for the development of MetS and CVD (60). The patients with NAFLD presented lower HDL cholesterol and higher indexes of adiposity (BMI, waist circumference/height ratio, subcutaneous and peritoneal fat) and IR than those with normal liver, and these factors are clustered in the definition of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors are also at risk of secondary cancers and recurrence of the primary cancer. [8][9][10][11][12][13][14][15] Despite the gravity of a cancer diagnosis, cancer patients do not always adhere to a healthy lifestyle. A survey of over 400,000 cancer survivors found that 15% were current cigarette smokers, 27.5% were obese, and 31.5% had not engaged in physical activity during the previous 30 days.…”
Section: ■ Effects Of Hematologic Cancer and Its Treatmentmentioning
confidence: 99%